Historical and epidemiological analyses on the impact of infectious disease on society - Greenberg, Edward Wertlieb, 1990- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2022)
"This book explores infectious disease from a variety of angles, including the humanities, the social sciences, and medicine and reflects the interaction of knowledge, and of human behavior, with the biology of disease processes"--